New religious movements in modern Asian history: sociocultural alternatives - Kim, David W.; Barker, Eileen (Ethnographies of religion, 2020)
The Ahmadiyya Muslim Jamaat : A New Religious Movement Derived from Islam? / Lauren Dover -- The Thánh Ngôn Hiệp Tuyẻ̂n: Translating and Understanding the Central Scripture of Caodaism / Christopher Hartney -- Dislocating Sōka Gakkai International : The Case of Sōka Gakkai International-Czech Republic / Petra Tlčimuková -- Scriptures and Their Restoration: A Case Study of Tenrikyō / Jiro Sawai.